2008
DOI: 10.1128/jb.00909-08
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of Growth Rate, ATP, and Pigmentation Suggests an Energy-Spilling Function for the Pigment Prodigiosin ofSerratia marcescens

Abstract: Serratia marcescens is a gram-negative environmental bacterium and opportunistic pathogen. S. marcescens expresses prodigiosin, a bright red and cell-associated pigment which has no known biological function for producing cells. We present here a kinetic model relating cell, ATP, and prodigiosin concentration changes for S. marcescens during cultivation in batch culture. Cells were grown in a variety of complex broth media at temperatures which either promoted or essentially prevented pigmentation. High growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 26 publications
4
60
0
2
Order By: Relevance
“…Another potential benefit for secondary metabolite regulation to be tied to a central metabolic regulator, cAMP-CRP, is suggested by Haddix et al; prodigiosin was shown to have a role in energy spilling that may protect cells at high culture density (43). Furthermore, recent work supports that prodigiosin has a positive effect on cell yield (P. Haddix, personal communication).…”
Section: Discussionmentioning
confidence: 75%
“…Another potential benefit for secondary metabolite regulation to be tied to a central metabolic regulator, cAMP-CRP, is suggested by Haddix et al; prodigiosin was shown to have a role in energy spilling that may protect cells at high culture density (43). Furthermore, recent work supports that prodigiosin has a positive effect on cell yield (P. Haddix, personal communication).…”
Section: Discussionmentioning
confidence: 75%
“…This study has demonstrated that sdhEygfX is a bicistronic operon, suggesting that these genes are functionally related, with both gene products affecting pig biosynthesis, directly or indirectly, at the level of transcription of the biosynthetic operon (pigA-O). This provides an additional link between carbon metabolism and the regulation of pig biosynthesis (11,45). Furthermore, deletion of sdhE affected multiple phenotypes, suggesting that multiple biological pathways might be affected.…”
Section: Discussionmentioning
confidence: 99%
“…This membrane-associated red pigment is produced by some biotypes of Serratia marcescens (16), a Gram-negative bacterium found in the rhizosphere (22,36), salt and fresh water, insect and mammal guts, and hospitals (16). Evidence suggests that prodigiosin functions in bacterial dispersal (5), competition against other organisms (14,59), regulation of proton gradients, energy, and pH homeostasis (21,41,44), and determination of surface hydrophobicity (42,43). Recent work has shown that prodigiosin has immunosuppressive and antitumor properties that may be of high clinical value (reviewed by Perez-Tomas and Vinas [38]).…”
mentioning
confidence: 99%